Increased Cell Traction-Induced Prestress in Dynamically Cultured Microtissues - van Kelle, Mathieu A. J.; Khalil, Nilam; Foolen, Jasper; Loerakker, Sandra; Bouten, Carlijn V. C. (Frontiers in Bioengineering and Biotechnology, 2019)
Prestress is a phenomenon present in many cardiovascular tissues and has profound implications on their in vivo functionality. For instance, the in vivo mechanical properties are altered by the presence of prestress, and prestress also inﬂuences tissue growth and remodeling processes. The development of tissue prestress typically originates from complex growth and remodeling phenomena which yet remain to be elucidated. One particularly interesting mechanism in which prestress develops is by active traction forces generated by cells embedded in the tissue by means of their actin stress ﬁbers. In order to understand how these traction forces inﬂuence tissue prestress, many have used microfabricated, high-throughput, micrometer scale setups to culture microtissues which actively generate prestress to specially designed cantilevers. By measuring the displacement of these cantilevers, the prestress response to all kinds of perturbations can be monitored. In the present study such, a microfabricated tissue gauge platform was combined with the commercially available Flexcell system to facilitate dynamic cyclic stretching of microtissues. First, the setup was validated to quantify the dynamic microtissue stretch applied during the experiments. Next, the microtissues were subjected to a dynamic loading regime for 24 hours. After this interval, the prestress increased to levels over twice as high compared to static controls. The prestress in these tissues is completely abated when a ROCKinhibitorwasadded, showingthatthedevelopmentofthisprestresscanbecompletelyattributed to the cell-generated traction forces. Finally, after switching the microtissues back to static loading conditions, or when removing the ROCK-inhibitor, prestress magnitudes were restored to original values. These ﬁndings show that intrinsic cell-generated prestress is a highly controlled parameter, where the actin stress ﬁbers serve as a mechanostat to regulate this prestress. Since almost all cardiovascular tissues are exposed to a dynamic loading regime, these ﬁndings have important implications for the mechanical testing of these tissues, or when designing cardiovascular tissue engineering therapies.